ITRAQ-based quantitative proteomic analysis of Fusarium moniliforme (Fusarium verticillioides) in response to Phloridzin inducers - Zhang, Rong (Proteome Sci, 2021)
BACKGROUND: Apple replant disease (ARD) has been reported from all major fruit-growing regions of the world, and is often caused by biotic factors (pathogen fungi) and abiotic factors (phenolic compounds). In order to clarify the proteomic differences of Fusarium moniliforme under the action of phloridzin, and to explore the potential mechanism of F. moniliforme as the pathogen of ARD, the role of Fusarium spp. in ARD was further clarified. METHODS: In this paper, the quantitative proteomics method iTRAQ analysis technology was used to analyze the proteomic differences of F. moniliforme before and after phloridzin treatment. The differentially expressed protein was validated by qRT-PCR analysis. RESULTS: A total of 4535 proteins were detected, and 293 proteins were found with more than 1.2 times (P< 0.05) differences. In-depth data analysis revealed that 59 proteins were found with more than 1.5 times (P< 0.05) differences, and most proteins were consistent with the result of qRT-PCR. Differentially expressed proteins were influenced a variety of cellular processes, particularly metabolic processes. Among these metabolic pathways, a total of 8 significantly enriched KEGG pathways were identified with at least 2 affiliated proteins with different abundance in conidia and mycelium. Functional pathway analysis indicated that up-regulated proteins were mainly distributed in amino sugar, nucleotide sugar metabolism, glycolysis/ gluconeogenesis and phagosome pathways. CONCLUSIONS: This study is the first to perform quantitative proteomic investigation by iTRAQ labeling and LC-MS/MS to identify differentially expressed proteins in F. moniliforme under phloridzin conditions. The results confirmed that F. moniliforme presented a unique protein profile that indicated the adaptive mechanisms of this species to phloridzin environments. The results deepened our understanding of the proteome in F. moniliforme in response to phloridzin inducers and provide a basis for further exploration for improving the efficiency of the fungi as biocontrol agents to control ARD. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12953-021-00170-2.